Lysophosphatidic acid signalling in development - Sheng, Xiaoyan (Development, 2015)
Lysophosphatidic acid (LPA) is a bioactive phospholipid that is present in all tissues examined to date. LPA signals extracellularly via cognate G protein-coupled receptors to mediate cellular processes such as survival, proliferation, differentiation, migration, adhesion and morphology. These LPA-influenced processes impact many aspects of organismal development. In particular, LPA signalling has been shown to affect fertility and reproduction, formation of the nervous system, and development of the vasculature. Here and in the accompanying poster, we review the developmentally related features of LPA signalling.